Mathematical models of spheroidal spiral-frame radiating structures - Dmitry P. Tabakov; Ruslan M. Valiullin (Физика волновых процессов и радиотехнические системы, 2023)
The article considers mathematical models of two spheroidal spiral-frame emitters, built on the basis of a general approach involving the use of an integral representation electromagnetic field. The internal problem of electrodynamics is reduced to a system of Fredholm integral equations of the 1st kind. The resulting system was solved by the method of moments with piecewise constant basis functions and delta functions as test functions. In this case, the local linearization of the generating conductors of the structures under consideration was carried out. The dependences of current distributions, input resistance, and radiation characteristics of structures on frequency have been studied. It is shown that standing, traveling, and mixed current waves can exist in the structures under consideration. The current regime is determined by the wave sizes and the geometry of the structures and determines the behavior of the wave resistance in the frequency range. Despite the similar geometry, the characteristics of the considered structures have certain differences.